N4-methylcytosine as a minor base in bacterial DNA. - Ehrlich, M (1987)
The DNA base composition, including the minor base content, of 26 strains of bacteria was determined. The studied bacteria are sources of widely used restriction endonucleases. Approximately 35% of the bacterial DNAs contained N4-methylcytosine, about 60% contained 5-methylcytosine, and about 90% had N6-methyladenine.